The Social Bases of Macrism: Actions and Claims of the Argentine Bourgeoisie, 2009-2015 - Sanz Cerbino, Gonzalo (2020)
We  intend  to  analyze  the  claims  and  actions  of  the  agricultural  and  industrial  fractions  of  the  Argentine  ruling  class  between  2008  and  2015  with  the  aim  of  reconstructing the origin of the alliance that drove the political change implemented in  2015.  We  will  analyze  the  actions  of  the  agricultural  and  industrial  interest  groups  and the fronts common to both; to do this we will combine a qualitative methodology  (to  analyze  positions  and  alliances)  with  a  quantitative  one  (to  analyze the protests). We will reconstruct diverse moments of conflict such as the agrarian dispute of 2008, the agrarian protests from 2009 to 2015, the formation of  an  industrial  opposition,  and  the  convergence  of  both  factions  in  the  2014  Business Convergence Forum, in which different fractions of the ruling class broke up with the government headed by Fernandez de Kirchner and went on to form the  opposition  alliance  This  reconstruction  will  allow  us  to  affirm,  in  contrast  to the dominant interpretations, that the main component of the government ́s opposition is not the agricultural bourgeoisie, whose weakness was evident in its inability to set itself up as a political alternative after 2008, but the big industrial bourgeoisie that as a result of joining the opposition in 2013 was able to tip the scales and trigger political change.